Multipurpose of radar / Nor Azery Abd. Rahim and Hazim Muhammad - Abd. Rahim, Nor Azery; Muhammad, Hazim (2003)
Final project is a part of course structure for student in their final year. The project is compulsory to us as a final year student for Diploma in Electrical Engineering The purpose of doing this project is to produce student mam power with a very skill and able to handle a responsibility that been given like this project. We should prepare to deliver a creativity idea and good interpersonal image to our future employee. By doing this project it will make student used all their knowledge, capability, creativity and skills to purpose create and trouble shoot the project It is because all of the theory and skills that they have learned from the project will be used in the future. In our project, before technology was founded, human sense something using eyes and ears. This multipurpose of radar is new technology of sense something that moving by the transducer that will detect and a pulse will be produced It depend a sensitivity setting and the direction of the movement